Performance Analysis of a Pure Sine Wave Inverter Using the EGS002 Module - Jhon Wandes P. Hutagaol; Ahmad Dani; Beni Satria (INFOKUM, 2025)
The development of renewable energy technology increases the need for efficient and reliable inverters to convert direct current into alternating current. This study aims to analyze the performance of a pure sine wave inverter using the EGS002 module as a pulse width modulation controller to produce a pure sine wave. The main issues studied are power conversion efficiency, output voltage stability, and total harmonic distortion (THD) under various load conditions, including resistive and non-linear loads. The research method involves experimental simulations using MATLAB/Simulink and Proteus software, by designing an inverter system based on the EGS002 module, IRF3205 MOSFET transistor, and LC filter. Performance parameters measured include power conversion efficiency (η), total harmonic distortion, and RMS output voltage (V_RMS). The simulation results show that the inverter achieves an average power conversion efficiency of 91.4%, total harmonic distortion below 5% under all load conditions, and output voltage stability with a deviation of less than 1% from the nominal value of 220 volts. These findings indicate that the EGS002 module is effective for inverter applications in renewable energy systems, although optimization is required for non-linear loads and production cost reduction. This research provides important insights for the development of more efficient and reliable inverters.